Microbiological Quality of Market Fruits and Their Handling Implication in Relation to Public Health - Alam, Mohammad Kamrul; Siddique, Mahbubul Pratik; Hossain, Muhammad Tofazzal; Rahman, Md Atawar; Khan, Md Shahidur Rahman (Microbes and Health, 2013)
The research study was conducted on the market fruits from selected local markets of Mymensingh, Bangladesh. The objectives of the study were to assess the microbiological quality of market fruits, hand washing and used water of hotels and chatpoti shops and to predict the comparative public health implication associated with the socioeconomic status of the inhabitants consuming the fruits and water. In fruit samples, the total viable count ranged from log 2.90 to log 6.4. No coliform bacteria were detected in fruit samples. Statistical analysis showed significant variations in microbial load in different fruits, hand washings and used water. Present study further demonstrated that there was lack of proper hygienic and sanitation measures in most of the markets, especially in town markets. Because of observed low sanitary quality, the urban market fruits should be handled and used with special attention to reduce the risk of contamination with potential pathogenic bacteria. DOI: http://dx.doi.org/10.3329/mh.v1i2.14095 Microbes and Health, 2012 1(2): 76-80